2013
DOI: 10.1002/ppul.22919
|View full text |Cite
|
Sign up to set email alerts
|

AMPK and FoxO1 regulate catalase expression in hypoxic pulmonary arterial smooth muscle

Abstract: Background: Hypoxia and reactive oxygen species (ROS) including H 2 O 2 play major roles in triggering and progression of pulmonary vascular remodeling in persistent pulmonary hypertension. Catalase (CAT), the major endogenous enzyme scavenging H 2 O 2 , is regulated in a tissue-and context-specific manner. Objective: To investigate mechanisms by which hypoxia and H 2 O 2 regulate catalase expression, and the role of AMPK-FoxO pathway, in neonatal porcine pulmonary artery smooth muscle (PASMC). Design/Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 60 publications
3
36
0
Order By: Relevance
“…A). AMPK activation in hypoxic situations is known to increase the cellular level of catalase (Sengupta et al ., ; Awad et al ., ). A lower level of catalase after short periods of ischaemia is consistent with the lower levels of AMPK activation that we have observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A). AMPK activation in hypoxic situations is known to increase the cellular level of catalase (Sengupta et al ., ; Awad et al ., ). A lower level of catalase after short periods of ischaemia is consistent with the lower levels of AMPK activation that we have observed.…”
Section: Resultsmentioning
confidence: 99%
“…Further evidence to support the AMPK activity alteration immediately after ischaemia, and during reperfusion comes from the results of testing one of the other main downstream substances of AMPK, which is catalase. There are several schools of thought, showing a direct link between activation of AMPK during hypoxia and increasing the level of cellular catalase (Awad et al, 2014). Sengupta et al (Sengupta et al, 2011) found that hypoxia/reperfusion increased the cardiomyocytes catalase through activation of AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…In response to hypoxia, we observed FoxO1 translocation into the nucleus in cardiomyocytes isolated from HFD‐fed mice. Our findings are consistent with results reported by recent studies showing that FoxO1 is mainly localized in the nucleus under hypoxic conditions in a variety of cell lines (Battiprolu et al ., ; Awad et al ., ). Analysis of subcellular localization of FoxO1 revealed that apelin‐13 promotes the retention of FoxO1 in the cytoplasm by preventing its nuclear translocation in response to oxygen deprivation.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the FoxO signaling pathway is associated with the apoptosis-resistant and hyperproliferative phenotype of PASMCs (31). Reactive oxygen species (ROS) is increased by hypoxia and activates AMPK-dependent regulation of FoxO1 expression, resulting in increased expression of catalase in PASMCs (43). Our study firstly uncovered that m 6 A influenced the stability of circRNAs, thus affecting the binding of circRNAs and miRNA, resulting in the activation of Wnt and FoxO signaling pathways.…”
Section: Discussionmentioning
confidence: 99%